The Analysis of Obligation Disputes on Returned Partnership Funds in Religious High Court of Medan - Cucu Susilawati Effendi (International Journal of Nusantara Islam, 2017)
This research is motivated by the partnership dispute on financing contract between PT. Bank Sumut Syariah;Branch Padang sidimpuan and Rip. Ongku Sutan Harahap. its dispute was occurred after the customer death,and so on causing the termination of the financing installment, because the financing is not covered by the insurance, so the bank asks the heir to be responsible for completing the remaining installment of the financing. The settlement of the dispute is settled through a litigation under the agreement of both parties to the dispute. The results of this study obtained that, PT. Bank Sumut Syariah Branch of Padangsidimpuan has neglected to apply the principle of prudence in the musyarakah (partnership) financing contract, namely disbursing financing funds without first being insured. Therefore, the Panel of Judges of  Medan Religious Court granted the heirs' petition. But the decision was canceled by the Medan High Religious Court, because the Panel of Judges found a formal defect in the form of obscuur libel, error in persona, disqualification in person. The formal defect resulted in the lawsuit not being accepted or N.O. (Niet Ontvankelijk verklaard). With the verdict N.O (Niet Ontvankelijk verklaard), the case becomes the quo status, it means back to its original state. Thus, the partnership (musyarakah) financing contract will remain valid and binding on both parties, their rights and obligations must be implemented in accordance with the contract.